Współczynnik Oporów Hydraulicznych w Gazociągach Dalekosiężnych - Walden, H. (Engineering Transactions, 1961)
On the basis of the research of the present and other authors the dependence of the coefficient of hydraulic resistance on the Reynolds number and the inner wall roughness is analysed for turbulent flow in long range gas pipe lines. The coefficient of resistance in smooth tubes is determined for various ranges of the Reynolds number from known hydraulic equations and from the present author’s empirical formula approaching the Blasius equation. In the transitory zone of the turbulent flow the author gives, besides of the equations of Nikuradse, Colebrook and White, Moody, his own generalized equation for the determination of the coefficients of resistance. For practical computations of the coefficients of resistance in the zone of quadratic dependence, a power equation should be applied which is equally accurate but more convenient.